A novel olecranon-type tracheotomy and expansion forceps for single-person emergency airway access - Zhu, Liang; Meng, Fanhao; Jin, Nenghao; Xing, Lejun; Wang, Yi; Zhang, Haizhong (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundWe developed olecranon-type tracheotomy and expansion forceps (OTEF) for emergency tracheotomy in patients experiencing acute airway obstruction. By using OTEF, medical rescue personnel can perform emergency tracheotomy more quickly and accurately on their own, while conventional tracheotomy requires the cooperation of two surgeons.MethodsIn this study, 24 adult cadavers that had died within 24 h were randomly assigned to the OTEF or PDT groups. Tracheotomies were performed by the same physician, using the OTEF technique for the OTEF group and the percutaneous dilational tracheotomy technique for the PDT group. The collected data included basic cadaver characteristics, operative time, incision length, and intraoperative tracheal wall injuries.ResultsIn the OTEF group, the mean tracheotomy completion time was 96.83 ± 8.82 s, with a mean incision length of 13.67 ± 3.67 mm. In the PDT group, the mean tracheotomy completion time was 566.50 ± 47.14 s, and the mean incision length was 20.67 ± 4.76 mm. Compared with the PDT group, the OTEF group demonstrated significantly shorter operative times (P < 0.05) and smaller incision lengths (P < 0.05).ConclusionOTEF enables efficient and minimally traumatic tracheostomies in emergency settings with minimal environmental and positioning requirements. In disaster sites or even on battlefields where medical personnel are in short supply, this device can enhance the battlefield rescue skills and emergency response capabilities of non-medical rescue workers, effectively alleviate rescue pressure and save the lives of the injured.